Estimate of organic carbon content in soils and vegetation of the State of Campeche. Methodological proposal - Pool-Novelo, Luciano; Kú-Quej, Víctor Manuel; Chí-Quej, Jesús; Mendoza-Vega, Jorge (REVISTA TERRA LATINOAMERICANA, 2019)
Assessing carbon content in soil and vegetation is a burdensome task, hence, the importance of developing reliable methods using databases with scarce information. The objective of the present study was to estimate the content of soil organic carbon (SOC) and organic carbon in vegetation (OCV) for the State of Campeche, Mexico. Developing a methodology in conditions of low availability of information. The off icial database available in Mexico (Instituto Nacional de Estadística y Geografía; INEGI) was used. The main limiting factor of the INEGI database for estimating the SOC by land unit area is the missing information on soil bulk density. Therefore, the bulk density of the soils was obtained using linear multiple regressions with data from 37 soil prof iles that were described in 10 of the 14 soil types reported in the State. The SOC ha-1 for each prof ile/soil unit for the whole State was calculated using the formula proposed by the Intergovernmental Panel on Climate Change. Estimation of OCV was achieved using INEGI database (area for vegetation type), reclassifying the vegetation types, from 58 to 23. The reduction of the coeff icient of variation in comparison with the results of other studies shows that the applied methodology produces more precise estimates. The total carbon estimated for the State of Campeche was 765 417 Gg, of which 64.1% accounted for SOC and 35.9% for OCV.